Packaging Information as Fact Versus Opinion: Consequences of the (Information-)Structural Position of Subjective Adjectives. Issue 7 (9th August 2021) - Kaiser, Elsi; Wang, Catherine
ABSTRACT: How do we distinguish fact from opinion? We tested whether people's ability to detect opinion-based content—as indicated by the use of subjective adjectives (e.g., amazing, frustrating )—depends on the linguistic position of the adjective. Our results show that simply changing the linguistic structure of a sentence influences our perception of the sentence's subjectivity: The same basic information, packaged differently in linguistic terms, yields significantly different subjectivity ratings. Specifically, our results show that texts with subjective adjectives in syntactic positions associated with new information and "main news" are rated as more opinion-based than texts conveying the same core information with the same adjective presented in a position that presents the information as already-known information or as secondary information. We also show that this information-packaging effect is independent of whether the sentence provides grounds/evidence for the opinion. More generally, our results suggest that linguistic-packaging choices can be used to blur the distinction between fact and opinion or, at least, our ability to perceive opinion-based information as such.